Sweden : Financial Sector Assessment Program Update-Detailed Assessment of Observance on NASDAQ OMX DM Observance of the CPSS-IOSCO Recommendations for Central Counterparties. (IMF Staff Country Reports; Country Report ;, 2011)
This paper is a detailed assessment of NOMX DM, undertaken in the context of the IMF Financial Sector Assessment Program (FSAP) Update for Sweden in 2011. NOMX DM, the only Central Counter-parties (CCP) in Sweden, has provided clearing services for equity, fixed income derivatives, and repo transactions since 2010. Even though NOMX DM has a comprehensive risk management framework, relevant points were brought up in the assessment related to governance and risk management. Swedish authorities have taken necessary measures to improve the system.